Senam Tai Chi, Kebugaran Fisik dan Kesehatan Psikologis Lansia: A Systematic Review - Milawati Milawati; Vivin Nur Hafifah (FORIKES, 2021)
Background: the aging process is a decline in body function so that it can interfere with the activities of the elderly. This of course can have an impact on decreasing psychological health to physical health in the elderly. Purpose: The purpose of this Systematic Review is to determine the effectiveness of Tai Chi exercises on physical fitness and psychological health in the elderly. Methods: Database search includes Google Scholar, Cambridge, and Proquest with the keyword the influence of Tai Chi gymnastics on physical health and the influence of Tai Chi gymnastics on psychological health. The criteria for the articles selected 2017-2021 are in full text and in English and speak Indonesian. This Systematic Review uses 15 articles that fit the inclusion criteria. Results: regular Tai Chi exercise can also improve the quality of life of the elderly and reduce or even eliminate the negative stigma in the elderly. Conclusion: Tai Chi exercise can improve physical health which tends to have problems and can reduce the risk of falling. This intervention can also improve the psychological health of the elderly and can change the stigma in families who think that the elderly are a burden in the familyKeywords: Tai Chi gymnastics; physical health; psychological health; the elderlyABSTRAKProses penuaan merupakan terjadinya kemunduruan fungsi tubuh sehingga dapat mengganggu aktivitas pada lansia. Hal ini tentu dapat berdampak menurunnya kesehatan psikologis hingga kesehatan fisik pada lansia. Tujuan dari Systematic Review ini adalah untuk mengetahui efektivitas senam Tai Chi terhadap kebugara fisik serta kesehatan psikologis pada lansia. Pencarian database meliputi Google Scholar, Cambridge, dan Proquest dengan kata kunci kunci the influence of Tai Chi gymnastics on physical health dan the influence of Tai Chi gymnastics on psychological health kriteria artikel yang dipilih 2017-2021 adalah dengan teks penuh dan berbahasa inggris dan berbahasa Indonesia. Systematic Review ini menggunakan 15 artikel yang sesuai dengan kriteria inklusi dengan total keseluruhan artikel yang diperoleh dalam pencarian sebayak 61 artikel (google scholar 37 artikel, Cambridge 10 artikel, dan PubMed 14 artikel). latihan senam Tai Chi secara rutin juga dapat meningkatkan kualitas kehidupan lansia dan mengurangi bahkan dapat menghilangkan stigma negative pada lansia. senam Tai Chi dapat meningkatkan kesehatan fisik yang cenderung meiliki masalah serta dapat mengursngi rsiko jatuh. intervensi ini juga dapat meningkatkan kesehatan lansia secara psikologis serta dapat merubah stigma pada keluarga yang beranggapan bahwa lansia merupakan beban dalam keluargaKata kunci: senam Tai Chi; kesehatan fisik; kesehatan psikologis; lansia